2017
DOI: 10.1021/acs.est.7b01002
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Byproduct Formation during Electrochemical Treatment of Latrine Wastewater

Abstract: Electrochemical systems are an attractive option for onsite latrine wastewater treatment due to their high efficiency and small footprint. While concerns remain over formation of toxic byproducts during treatment, rigorous studies examining byproduct formation are lacking. Experiments treating authentic latrine wastewater over variable treatment times, current densities, chloride concentrations, and anode materials were conducted to characterize byproducts and identify conditions that minimize their formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
121
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 45 publications
11
121
3
1
Order By: Relevance
“…[2,13,17] This behavior is attributed to the formation of highly refractory organochlorinated byproducts which are very difficult to mineralize. [70] Another drawback of the presence of Cl À ions in wastewater during electrooxidation is the high risk of production of highly toxic chlorinated amines, [111,112] trihalomethanes (THMs) and haloacetic acids (HAAs) [102,[113][114][115][116][117] as well as hazardous perchlorate from the oxidation of organic pollutants by electrogenerated RCS. [70,88] However, at higher Cl À concentrations, lower mineralization rate is always observed due to the formation of larger quantity of recalcitrant organochlorinated byproducts that are highly resistant to the oxidation by electrogenerated BDD( * OH).…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…[2,13,17] This behavior is attributed to the formation of highly refractory organochlorinated byproducts which are very difficult to mineralize. [70] Another drawback of the presence of Cl À ions in wastewater during electrooxidation is the high risk of production of highly toxic chlorinated amines, [111,112] trihalomethanes (THMs) and haloacetic acids (HAAs) [102,[113][114][115][116][117] as well as hazardous perchlorate from the oxidation of organic pollutants by electrogenerated RCS. [70,88] However, at higher Cl À concentrations, lower mineralization rate is always observed due to the formation of larger quantity of recalcitrant organochlorinated byproducts that are highly resistant to the oxidation by electrogenerated BDD( * OH).…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
“…[70,88] However, at higher Cl À concentrations, lower mineralization rate is always observed due to the formation of larger quantity of recalcitrant organochlorinated byproducts that are highly resistant to the oxidation by electrogenerated BDD( * OH). [106,[121][122][123] Radjenovic group [106,116,124,125] have carried out extensive works on identification and quantification of generated halogenated byproducts in different media during the electrooxidation of electrodialyzed/non-electrodialyzed ROC using different electrode materials. [118][119][120] Indeed, several studies have reported the formation and accumulation of total adsorbed organic chloride and bromide especially during the treatment of ROC.…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
See 3 more Smart Citations